2016
DOI: 10.18632/oncotarget.9539
|View full text |Cite
|
Sign up to set email alerts
|

Screen-identified selective inhibitor of lysine demethylase 5A blocks cancer cell growth and drug resistance

Abstract: Lysine demethylase 5A (KDM5A/RBP2/JARID1A) is a histone lysine demethylase that is overexpressed in several human cancers including lung, gastric, breast and liver cancers. It plays key roles in important cancer processes including tumorigenesis, metastasis, and drug tolerance, making it a potential cancer therapeutic target. Chemical tools to analyze KDM5A demethylase activity are extremely limited as available inhibitors are not specific for KDM5A. Here, we characterized KDM5A using a homogeneous luminescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 36 publications
1
69
0
Order By: Relevance
“…KDM5 family proteins, KDM5A (RBP2), KDM5B (PLU1), KDM5C (SMCX) and KDM5D (SMCY), are mammalian demethylases for trimethylated lysine 4 of histone H3 (H3K4me3), an epigenetic mark associated with transcriptional activation (4649). KDM5D is located on the Y chromosome, so only KDM5A, 5B and 5C H3K4me3 demethylases are present in cells isolated from females.…”
Section: Resultsmentioning
confidence: 99%
“…KDM5 family proteins, KDM5A (RBP2), KDM5B (PLU1), KDM5C (SMCX) and KDM5D (SMCY), are mammalian demethylases for trimethylated lysine 4 of histone H3 (H3K4me3), an epigenetic mark associated with transcriptional activation (4649). KDM5D is located on the Y chromosome, so only KDM5A, 5B and 5C H3K4me3 demethylases are present in cells isolated from females.…”
Section: Resultsmentioning
confidence: 99%
“…Histone demethylases and their associated chromatin modulations have been linked to EGFR TKIs resistance in NSCLC cells (24,25). In addition, PLU-1 has been reported to promote drug resistance in melanomas (26) and to drive metastasis and EMT in hepatocellular cancer cells (27), while LSD1 has been shown to promote invasion and metastasis through facilitating EMT in many cancer cell types (2830).…”
Section: Resultsmentioning
confidence: 99%
“…6D), supporting the notion that the demethylase activity of KDM5 family members is involved in APA regulation of DICER1 . To determine which KDM5(s) contribute to this regulation, we deleted KDM5A, KDM5B, and KDM5C individually using an inducible CRISPR (clustered regularly interspaced short palindromic repeats) system ( 51 , 52 ) and found that deletion of KDM5A or KDM5B, but not KDM5C, decreased 3′UTR length of DICER1 (Fig. 6E), suggesting that both KDM5A and KDM5B are involved in APA regulation.…”
Section: Resultsmentioning
confidence: 99%